Biomimetic Nanozymes Based on Coassembly of Amino Acid and Hemin for Catalytic Oxidation and Sensing of Biomolecules. Issue 19 (24th March 2021) - Geng, Rui; Chang, Rui; Zou, Qianli; Shen, Guizhi; Jiao, Tifeng; Yan, Xuehai
Abstract: Nanoassemblies based on self‐assembly of biological building blocks are promising in mimicking the nanostructures, properties, and functionalities of natural enzymes. However, it remains a challenge to design of biomimetic nanozymes with tunable nanostructures and enhanced catalytic activities starting from simple biomolecules. Herein, the construction of nanoassemblies through coassembly of an amphiphilic amino acid and hemin is reported. The nanostructures and morphologies of the resulting nanoassemblies are readily controlled by tuning the molar ratio between the amino acid and hemin, thus leading to tailored peroxidase‐mimicking activities of the nanoassemblies. Importantly, the optimized nanoassemblies exhibit a remarkable catalytic efficiency that is comparable to the natural counterpart when considering molecular mass along with good robustness in multiple catalytic cycles. The nanoassemblies are effectively integrated as biomimetic nanozymes in a sensing system for catalytic detection of glucose. Therefore, this work demonstrates that nanozymes with advanced catalytic capabilities can be constructed by self‐assembly of minimalist biological building blocks and may thus promote the rational design and catalytic applications of biomimetic nanozymes. Abstract : Simple but complex: Biomimetic nanozymes with adjustable nanostructures, morphologies, and catalytic performances are facilely constructed by coassembly of minimalist biological building blocks, an amino acid derivative and hemin. The nanozymes exhibit a remarkable catalytic efficiency comparable to the natural horseradish peroxidase and show typical enzyme‐like characteristics in catalytic sensing of glucose.